Effect of gender on outcome of out of hospital cardiac arrest in the Resuscitation Outcomes Consortium. (March 2016) - Morrison, Laurie J.; Schmicker, Robert H.; Weisfeldt, Myron L.; Bigham, Blair L.; Berg, Robert A.; Topjian, Alexis A.; Abramson, Beth L.; Atkins, Dianne L.; Egan, Debra; Sopko, George; Rac, Valeria E.; ,
Abstract: Introduction: This study examined the relationship between gender and outcomes of non-traumatic out-of-hospital cardiac arrest (OHCA). Methods: All eligible, consecutive, non-traumatic Emergency Medical Services (EMS) treated OHCA patients in the Resuscitation Outcomes Consortium between December 2005 and May 2007. Patient age was analyzed as a continuous variable and stratified in two age cohorts: 15–45 and >55 years of age (yoa). Unadjusted and adjusted (based on Utstein characteristics) chi square tests and logistic regression models were employed to examine the relationship between gender, age, and survival outcomes. Results: This study enrolled 14, 690 patients: of which 36.4% were women with a mean age of 68.3 and 63.6% of them men with a mean age of 64.2. Women survived to hospital discharge less often than men (6.4% vs. 9.1%, p < 0.001); the unadjusted OR was 0.69, 95%CI: 0.60, 0.77 whereas when adjusted for all Utstein predictors the difference was not significant (OR: 1.16, 95%CI: 0.98, 1.36, p = 0.07). The adjusted survival rate for younger women (15–45 yoa) was 11.1% vs. 9.8% for younger men (OR: 1.66, 95%CI: 1.04, 2.64, p = 0.03) but no difference in discharge rates was observed in the >55 cohort (OR: 0.94, 95%CI: 0.78, 1.15, p = 0.57). Conclusions: Women who suffer OHCAs have lower rates of survival and have unfavourable Utstein predictors. When survival is adjusted for these predictors survival is similar between men and women except in younger women suggesting that age modifies the association of gender and survival from OHCA; a result that supports a protective hormonal effect among premenopausal women.